PEMODELAN DAN SIMULASI SISTEM PENDINGIN UDARA PADA RUANG PENUMPANG, KRU, DAN ANJUNGAN KAPAL PENUMPANG SABUK NUSANTARA - Yudhistira Fajar Farabi (2022)
The room temperature inside the ship affects the comfort level of passengers, crew, and equipment on board, so the temperature inside the vessel is set in ISO 7547, which is a maximum of 27°C. So it is necessary to know each room's cooling loads. The cooling load includes; the size of the room, the coefficient of heat transmission, the temperature in the next room, the area exposed to heat, the coefficient of the heat source, the number of people in the room, the number of equipment that generates heat, and the number of people in the room, lighting in the room. In this study, CoolPack software is used to calculate the required cooling load, and the ADF BAS System is used to simulate the air conditioning model that has been modeled